Neural correlates of theory-of-mind reasoning: an event-related potential study. - Sabbagh, Mark A.; Taylor, Marjorie (Psychological Science., 2000)
A study was conducted to examine neural correlates of theory-of-mind reasoning. Data were gathered from a sample of 23 right-handed students who were required to participate in an experimental task. The results reveal that the neural activity activated by tasks that required thinking about mental as compared to non-mental representations was characterized by a focally enhanced positivity over left frontal areas, which was diminished over left parietal areas. The findings offer an important perspective on both children's theory-of-mind development and the neurobiology of disorders in which theory of mind appears to be damaged.